DETERMINATION OF BEARING CAPACITY OF OPEN ENDED STEEL SINGLE PILES - HAWES, TOLAZ SALAH (Fırat Üniveristesi, 2021)
Açık uçlu kazıklar genellikle açık deniz ve kıyı yapılarının temellerinde, yükleri taşıma gücü düşük üst toprak tabakalarından daha sağlam alt toprak tabakalarına aktarmak için kullanılmaktadır. Açık uçlu kazıklar, diğer kazık türlerine göre daha düşük çakma direncine sahip olduğundan kullanımları önem kazanmıştır. Bu çalışmada diyafram yüksekliği 7,5 cm (Tip A) ve diyafram yüksekliği 10 cm (Tip B) olan iki açık uçlu kazığın taşıma kapasiteleri karşılaştırılmıştır. Kazıklar, dört farklı rölatif sıkılıkta (%10, %40, %65, %90) hazırlanan zeminler içerisinde deneye tabi tutulmuştur. Deneylerde her bir rölatif sıkılık için yük-oturma eğrisi elde edilmiştir. Deneysel sonuçlar, deneyde kullanılan iki kazıkta da rölatif sıkılık arttıkça taşıma kapasitesinin arttığını ve açık uçlu kazıkların taşıma kapasitesinin kazık diyafram boyunun artmasıyla arttığını göstermiştir. Yapılan deneysel çalışma ile bulunan sonuçları ve verileri doğrulamak için Plaxis 3D sonlu elemanlar programı kullanılmıştır. Bu program kullanılarak kazık sistemi modellenmiş ve ayrıca program ile elde edilen yük-oturma eğrileri deneysel sonuçlarla karşılaştırılmıştır.

Open-ended piles are generally used in foundation to build super structure building such as offshore engineering and the coastal that is used to transfer the load through the upper weak top soil layer to the stronger layer of subsoil strata. Open-ended piles are very important for using, due to it has smaller driving resistance compared to other types of the pile. In this study, the bearing capacity of two open-ended piles, one with a diaphragm height of 7.5cm (Type A) and the other with a 10cm (Type B) diaphragm height, is compared. The piles are tested using a special test system for soils prepared at four different relative densities (10%, 40%, 65%, 90%). The load-settlement curve for each relative density has been obtained as a result of the experiments. Experimental results indicated that bearing capacity of two piles used in the test increase with increasing relative density and the bearing capacity of open-ended pile increasing with increasing dimension of the diaphragm of the pile. To verify the results and data which have been found by experimental study, Plaxis 3D finite element program is used in this study. The pile system was modeled by using the program and also the program has found load-settlement curve to compare with the experimental results.
Açık uçlu çelik tekli kazıkların taşıma kapasitesinin belirlenmesi
Keywords: İnşaat Mühendisliği